PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN KONSUMEN DALAM MEMBELI HANDPHONE NOKIA DI KECAMATAN ENDE SELATAN KABUPATEN ENDE - Yosef Tonce; Kristina Sujila (Universitas Nusa Nipa Maumere, 2025)
Nowadays, the development of the world of technology and information has a great influence on our daily lives. This is marked by the increasing number of new products circulating in the market. To be able to win market share of sales, a strategy is needed. One of the strategies carried out by the company is with a marketing mix pattern consisting of products, prices, venues and distribution. The most used product is Nokia Mobile Phones. To determine the analysis of the influence of the free bound variable, multiple regression analysis was used through a computer with the SPSS Release program with a validity and realiginess test The coefficient of determination (R square) was 0.793. But the number of variables is more than two, then an adjudted square of 0.726 is used, meaning that the change Y (buying decision) is determined by a free variable of 72.6%. The correlation coefficient of the overall independent variable (multiple R) is 0.891 or 8.9%, meaning that the relationship between the purchase decision and the independent variable is strong. Based on the analysis, it can be concluded that the influence of the marketing mix on consumer decisions in buying Nokia Mobile phones in South Ende District, Ende Regency can be said to be very influential Thus the expected target for the public to decide to buy products with trusted brands so that consumer satisfaction can be trusted.